The changing political economies of small West European countries - Becker, Uwe, 1951- (Changing welfare states., 2011)
"The literature on changing varieties of capitalism concentrates on the big economies, particularly the US, Japan and Germany. This important volume sheds light on the group of smaller European countries that share a high degree of corporatism - Austria, Belgium, Denmark, Finland, the Netherlands, Norway, Sweden and Switzerland. Most of them have recently been praised as alter native models to the route exemplified by the US. The authors investigate the trajectories of these countries welfare systems, corporate governance, labour markets and industrial relations from about 1990 until the economic crisis in 2008. The volume also tracks their position in the processes of European integration and asks whether their particular brands of capitalism might be a viable candidate for the European socio-economic model."--Provided by publisher